Psychosocial factors associated with talent development in football: A systematic review. (July 2017) - Gledhill, Adam; Harwood, Chris; Forsdyke, Dale
Abstract: Objectives: To provide a critical systematic review of recent research into psychosocial factors associated with talent development in football. Design: Systematic review informed by the PRISMA guidelines. Method: Literature was sourced from Science Direct, Sport Discus, Psycharticles and Psychinfo. This was followed by a detailed screening and sifting process to identify literature. Identified literature was independently appraised by multiple reviewers using the mixed-methods Appraisal Tool (MMAT). Data was represented using concept mapping. Results: Forty-three studies met the inclusion criteria. They investigated a cumulative 14, 977 participants and gleaned 48 psychosocial factors associated with talent development in football. Findings suggest that social and psychological factors are interrelated and influence adaptive developmental behaviours (e.g., adaptive lifestyle choices, practice and play behaviours). These can influence coach perceptions of players and whether they may recommend players for career progression. Independent MMAT appraisal demonstrated a moderate risk of bias. Female football players and female coaches are significantly under-represented in the literature; with white, adolescent, able-bodied, male European football players dominating the literature. Descriptive, cross-sectional, correlational and retrospective designs are most commonly adopted in the literature. Conclusions: Psychosocial factors can differentiate between performance levels of football or are positively associated with career progression to a senior elite level in football, however findings should be viewed with caution due to a moderate risk of bias in reporting. The research area would be advanced by diversification of participant groups, longitudinal, prospective designs, and by testing the predictive validity of existing grounded theories. Highlights: We reviewed psychosocial factors associated with talent development in football. We created a concept map of hypothesized relationships between these factors. We noted five behavioural indicators of talent development in football. Independent study appraisals using MMAT show a moderate risk of reporting bias. Female players and female coaches are underrepresented in the literature.